Classroom Climate and Student’s Academic Performance of a Public School in Antique - Gentova, Cecile S.; Madrigal, Dennis V. (Philippine Social Science Journal, 2020)
Classroom climate is a comprehensive set of educational, psychological, social, cognitive, organizational, and physical variables that may affect the academic achievement of learners. Perceptions of students in their learning environment affect the way they perform in the classroom. However, classroom climate is a less explored construct creating much dearth on the local literature. Hence, the paper aimed to determine the degree of classroom climate in terms of discipline, learning, assessment, student interactions, attitude, and culture. Moreover, it also assessed if a significant difference exists when assessors are grouped according to the designation. Likewise, it determines the correlation between classroom climate and academic performance of junior high school students in a public school in Antique.